2013
DOI: 10.5271/sjweh.3363
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual heuristic models of the interrelationships between obesity and the occupational environment

Abstract: Pandalai SP, Schulte PA, Miller DB. Conceptual heuristic models of the interrelationships between obesity and the occupational environment. Scand J Work Environ Health. 2013;39(3):221-232. doi:10.5271/sjweh.3363 Objective Research and interventions targeting the relationship between work, its attendant occupational hazards, and obesity are evolving but merit further consideration in the public health arena. In this discussion paper, conceptual heuristic models are described examining the role of obesity as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 131 publications
1
30
0
Order By: Relevance
“…Furthermore, an elevated body mass index is characterized by a reduced tolerance to effort and lack of satisfaction (Pagoto et al, 2006;Singh et al, 2009 Aug), a reduced executive function performance (Gunstad et al, 2007), a reduced muscle strength normalized per body weight and lower tolerance to prolonged postures and sleep disturbances (Pandalai et al, 2013;Di Lorenzo et al, 2003;Costa, 2010;Singh et al, 2009 Aug;Cavuoto and Nussbaum, 2013), which could explain the underlying mechanisms between obesity and lower WF in the working population, especially in shift-workers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, an elevated body mass index is characterized by a reduced tolerance to effort and lack of satisfaction (Pagoto et al, 2006;Singh et al, 2009 Aug), a reduced executive function performance (Gunstad et al, 2007), a reduced muscle strength normalized per body weight and lower tolerance to prolonged postures and sleep disturbances (Pandalai et al, 2013;Di Lorenzo et al, 2003;Costa, 2010;Singh et al, 2009 Aug;Cavuoto and Nussbaum, 2013), which could explain the underlying mechanisms between obesity and lower WF in the working population, especially in shift-workers.…”
Section: Discussionmentioning
confidence: 98%
“…These costs include direct health care costs and indirect costs, of which most are related to presenteeism (lost productivity at work) (Muller-Riemenschneider et al, 2008). It is also known that the major occupational health problems such as musculoskeletal disorders, mental disorders and cardiovascular diseases, are directly or indirectly associated with obesity (Pandalai et al, 2013), and thus could negatively affect productivity or functioning at work.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of information is a significant barrier to establishing an effective and comprehensive worksite strategy for prevention of obesity in professional firefighters by integrating health protection (occupational safety and health) with health promotion approaches [Hymel et al, 2011]. The etiology of obesity is multifactorial involving significant environmental factors, including physical and psychosocial working conditions, culture, and socioeconomic status [Davidson and Knafl, 2006;Choi et al, 2011;Agne et al, 2012;Pandalai et al, 2013]. Several epidemiological studies have reported associations of adverse working conditions with obesity in general working populations and other occupational groups, albeit not supported in some studies [Ghiasvand et al, 2006;Lallukka et al, 2008;Pulsford et al, 2013]: low work-related physical activity (e.g., sedentary work) [Mummery et al, 2005;Choi et al, 2010]; shift work [van Amelsvoort et al, 1999;Kubo et al, 2011;Macagnan et al, 2012]; long working hours [Di and Mummery et al, 2009;Solovieva et al, 2013;Jang et al, 2014;Luckhaupt et al, 2014;Lemke et al, 2015]; and low organizational support for employee heath [Tabak et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the role of obesity as a risk factor for cancer and type 2 diabetes has been explored in occupational settings (33). This integrated and comprehensive approach maximizes program success and potential for sustainability over time.…”
Section: Integrating Health Protection and Health Promotionmentioning
confidence: 99%